Design and Validation of the Inventory for Soft Skills in Secondary Education Students: IHBE (Praxis Educativa, 2026)
The objective of this study was to design an inventory for teacher use to assess soft skills in secondary schoolstudents. The process included validation by expert judgment, a pilot test with 25 questionnaires, and adaptation.Subsequently, a non-probability sample was applied to 420 students (47% female, 53% male) between the agesof 12 and 19 (ME = 14.92; SD = 1.81). Initially, a parallel analysis suggested a four-factor structure of the IHBE.Exploratory factor analysis identified items with psychometric complexity, so 16 items were retained. The16-item version measures four factors: interpersonal, social, intellectual, and accuracy skills. Semi-confirmatoryfactor analysis yielded goodness-of-fit indices (GFI = .98, AGFI = .96, RMSA = .000) with a 95% confidenceinterval. The IHBE showed high internal consistency (α = .97, .95, .85, and .90 for each factor; 97 for the totalinstrument). The results of the theoretical model support the validity and reliability of the preliminary version ofthe IHBE.
Keywords: classroom diagnoses; secondary schools; soft skills; inventory; educational projects